Cobalt Diazo‐Compounds: From Nitrilimide to Isocyanoamide via a Diazomethanediide Fleeting Intermediate. (8th April 2021) - Aghazada, Sadig; Fehn, Dominik; Heinemann, Frank W.; Munz, Dominik; Meyer, Karsten
Abstract: Lithium trimethylsilyldiazomethanide and a cobalt (II) precursor with an N‐anchored tris ‐NHC (TIMEN mes ) ligand provide access to the cobalt nitrilimide 1 . Complex 1 was structurally characterized by single‐crystal X‐ray diffractometry (SC‐XRD) and its electronic structure was examined in detail, including EPR spectroscopy, SQUID magnetometry and computational analyses. The desilylation of the C ‐(trimethylsilyl)nitrilimide reveals a transient complex with an elusive diazomethanediide ligand, which substitutes one of the mesitylene rings of the ancillary ligand through C−N bond cleavage. This transformation results in the cyclometalated cobalt(II) complex 2, featuring a rare isocyanoamido‐κ‐C ligand. Abstract : Trimethylsilylium abstraction from a cobalt nitrilimide complex generates a transient cobalt diazomethanediide complex, which forms a terminal isocyanoamido ligand through a radical de‐arylation.